2017
DOI: 10.1039/c6mb00830e
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling study of shikonin's cytotoxic activity in the Huh7 human hepatoma cell line

Abstract: Shikonin and its enantiomer alkannin, which are natural products, have been extensively studied in vitro and in vivo for, among others, their antitumor activity. The investigation of the molecular pathways involved in their action is of interest, since they are not yet clearly defined. Metabolic profiling in cells can provide a picture of a cell's phenotype upon intervention, assisting in the elucidation of the mechanism of action. In this study, the cytotoxic effect of shikonin on a human hepatocarcinoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Our group investigated the inhibition of c-MYC expression and transcriptional activity by shikonin as a novel mechanism for killing leukemia cells [9], and more recently, the cytotoxic activity of shikonin to the Huh7 cancer cell line by a metabolite profiling approach which could set a basis for the elucidation of their antitumor activity was investigated [13]. Shikonin has also been proposed as a novel dietary agent with great potential in breast cancer prevention [14] and has been found to act synergistically to potentiate doxorubicin-induced growth inhibition and apoptosis in vitro [15].…”
Section: Introductionmentioning
confidence: 99%
“…Our group investigated the inhibition of c-MYC expression and transcriptional activity by shikonin as a novel mechanism for killing leukemia cells [9], and more recently, the cytotoxic activity of shikonin to the Huh7 cancer cell line by a metabolite profiling approach which could set a basis for the elucidation of their antitumor activity was investigated [13]. Shikonin has also been proposed as a novel dietary agent with great potential in breast cancer prevention [14] and has been found to act synergistically to potentiate doxorubicin-induced growth inhibition and apoptosis in vitro [15].…”
Section: Introductionmentioning
confidence: 99%
“…MCF7MX cells presented chemotoleration features for mitoxantrone cytotoxicity during both shikonin treatments even though BCRP pump activity was significantly (P < 0.001) blocked during the experiment time. Such behaviors may be attributed to alteration of metabolism pathways of cancer cells associated with energy consumption, chemotherapeutics metabolism and physicochemical inactivation of the hydroxyl naphthoquinones in this cell 36 , 38 . Our initial investigations demonstrated that chemosensitization and MDR-associated efflux blockage are less likely dependent on shikonin dosage volumes; such separate activities support the hypothesis that shikonins are uncompetitive pump blockers.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is a key mediator transferring extracellular signals into cell nucleus to regulate various cellular processes including proliferation, apoptosis, angiogenesis, and other biological activities. [23][24][25][26] The activation of STAT3 is through the phosphorylation of the Tyr705 residue in SH2 domain and contributes to carcinogenesis and tumor progression when the activation is aberrantly up-regulated. [27,28] Great efforts have been devoted to identify potent inhibitors that hold promise for suppressing STAT3 activation, of which a considerable proportion is comprised by various naphthoquinones.…”
Section: Via Stat3 Inhibitionmentioning
confidence: 99%
“…Of interest is the performance of naphthoquinone scaffold in the development of selective STAT3 (signal transducer and activator of transcription 3) inhibitors. STAT3 is a key mediator transferring extracellular signals into cell nucleus to regulate various cellular processes including proliferation, apoptosis, angiogenesis, and other biological activities . The activation of STAT3 is through the phosphorylation of the Tyr705 residue in SH2 domain and contributes to carcinogenesis and tumor progression when the activation is aberrantly up‐regulated .…”
Section: Via Stat3 Inhibitionmentioning
confidence: 99%